Seeing the Forest for the Trees: Threats, Vulnerabilities, and Opportunities for Woody Landscape Plant Genetic Resources - Margaret Pooler; Ryan C. Contreras; Richard A. Criley; Michael S. Dosmann; Russell Galanti; Stan C. Hokanson; Brandon M. Miller; Bryan J. Peterson; Madhugiri Nageswara-Rao; Todd J. Rounsaville; Jacob H. Shreckhise; Todd P. West; et al. (HortScience, 2024)
Genetic resources are the foundation of American agriculture’s ongoing success—the diversity, security, health, and genetic integrity of these resources must be safeguarded. However, in contrast to other crops, protecting, managing, and using collections of woody landscape plant genetic resources present significant challenges. These include conservation of at-risk populations that have high genetic diversity, evaluation of taxa with an unknown potential to invade, and management of large specimens that have long generation times and often recalcitrant or difficult-to-store seeds. The wide diversity of taxa and the limited number of specialist curators and scholars present further challenges. Thus, effective collection, preservation, evaluation, and distribution of woody landscape plant germplasm require substantial and specialized resources. The most fundamental challenge is simple: too many built landscapes have low taxonomic diversity and are often dominated by a single taxon, or monoculture. In turn, these taxonomically and genetically depauperate landscapes are vulnerable to a host of biotic and abiotic threats and are less likely to provide ecosystem and societal services for which they were designed. To develop more resilient landscapes, there is an urgent need to expand taxonomic diversity, which requires the horticultural community to effectively acquire, curate, evaluate, distribute, and use diverse woody landscape plant genetic resources. The role of the US Department of Agriculture-Agricultural Research Service (USDA-ARS) National Plant Germplasm System (NPGS) Woody Landscape Plant Crop Germplasm Committee (WLPCGC) is to identify vulnerabilities and threats that compromise WLP crops in the United States and make recommendations for prioritization of germplasm acquisition, evaluation, research, and management priorities through regular interaction with stakeholders. Due to the breadth of genera and shifting plant genetic resource needs of the nursery industry, it is impractical to list specific threatened or priority genera in a broadly applicable crop vulnerability statement. Instead, the WLPCGC has identified themes of threats and vulnerabilities providing a foundation upon which to support prioritization as threats to specific genera emerge.